Willingness to pay for threatened and endangered marine species: a review of the literature and prospects for policy use - Lew, Daniel K. (Frontiers in Marine Science, 2015)
Non-market valuation methods have been employed to estimate willingness to pay for numerous threatened, endangered, and rare (TER) species over the past few decades. While most of these efforts have focused on terrestrial species, over 30 published studies have been conducted to measure economic values associated with the preservation, protection, and enhancement of scores of marine species. In this paper, this literature is reviewed and assessed, and an evaluation of the suitability of existing TER species values as inputs for the analysis of marine and coastal policies, and the prospects and challenges for improving them, are discussed. The published literature is found to suffer from coverage issues, both geographical and in terms of species types. It includes stated preference valuation studies focused on marine species only in developed countries (United States, Canada, Australia, United Kingdom, Spain, and Greece), with the highest concentration of studies occurring in the United States. The species valued primarily can be classified as charismatic megafauna—seals and sea lions, whales, and sea turtles—plus well-known fish species, like salmon. Only a small handful of lesser known species are included among those valued to date. Species value estimates were as much as $356 (2013 U.S. dollars), but differed in the frequency of payments (e.g., lump sum vs. annual), the entity paying (e.g., household, resident, or visitor), and the specific good being valued (e.g., species preservation or a type of enhancement). Potential sources of errors arising from the use of these values for policy analyses, and the temporal stability of them, provide reasons to be cautious in their application. Nevertheless, several trends in the literature appear to provide reasons to be optimistic about the literature, particularly the recent expansion of types of species valued and more policy-relevant values.